2003
DOI: 10.1007/s00170-002-1437-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of optimum clearance in sheet metal blanking processes

Abstract: The blanking process and structure of the blanked surface are influenced by both the tooling (clearance and tool geometry) and properties of the workpiece material (blank thickness, mechanical properties, microstructure, etc.). Therefore, for a given material, the clearance and tool geometry are the most important parameters. The objective of the present work is to develop a methodology to obtain the optimum punch-die clearance for a given sheet material by simulation of the blanking process. A damage model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This FEM code is based on an implicit Lagrangian computational routine [18]. The blanking process was considered axisymmetric, and a 2D model was used to simulate the process parameters.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This FEM code is based on an implicit Lagrangian computational routine [18]. The blanking process was considered axisymmetric, and a 2D model was used to simulate the process parameters.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…proposed using a FEM method and neural network analysis to optimize the clearance between punch and die [17] and [18]. Mole et al [19] proposed a new FEM method to optimize the blank shape.…”
Section: Introductionmentioning
confidence: 99%
“…Through literature, it is clear that many methods are used to study the blanking process to achieve the optimal combination of its parameters. This includes analytical approaches [6,7]; Finite Element Method [8, 9, and 10]; Design of Experiments [1,10] and Neural Networks Modeling [11]. Literature shows that the mechanical characteristics of the blanking process and the geometrical aspect of the sheared edge are affected by different parameters.…”
Section: 15mentioning
confidence: 99%
“…Some of the previous experiments have been done by experimenters to formulate certain hypotheses about a particular process. Hambli et al [15] found that the design of experiment technique is an efficient and cost-effective way to model and analyze the interactions which indicate process variations. DOE also has wide application in the improvement of new processes in such a way that processes can be defined based on several controllable variables.…”
Section: Introductionmentioning
confidence: 99%